ANALISIS PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, STRUKTUR ASET DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN HUTANG - Sari, Ristiana Inda; Suhendro, Suhendro; Dewi, Riana Rachmawati (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2021)
ABSTRACT This study aims to examine and analyze the effect of profitability, firm size, asset structure, and managerial ownership on debt policy. The method in this research is quantitative. The sample selection used a purposive sampling method so as to obtain a sample of 21 property, real estate, and building construction companies listed on the Indonesia Stock Exchange (BEI) in 2015-2019. The data used in this research is secondary data. The data analysis method used is multiple regression analysis. The results showed that profitability and firm size had an effect on debt policy. Meanwhile, the asset structure and managerial ownership have no effect on debt policy. Keywords: Profitability, Firm Size, Asset Structure, Managerial Ownership, Debt Policy